Konseling Pranikah Untuk Meminimalisir Masalah-Masalah Pranikah Bagi Calon Pengantin - Alfaiz, Alfaiz; Sari, Azmatul Khairiyah; Zahri, Triave Nuzila; Erezka, Roshinta; Yudhy, Yudhy; Wiryawan, M. Ryzki; Rafiola, Ryan Hidayat (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2023)
Marriage is the Sunnah of the Prophet to be followed for couples who already have feelings of love in their hearts. Marriage is a means to channel love in a lawful manner. The marriage that every couple wants is a perfect marriage without any flaws. Prospective brides will try to prepare for married life as well as possible. On the day of the wedding, they will invite relatives, family and friends to enliven their party. Everything was prepared as perfectly as possible. Live a marriage with a happy and comfortable feeling because the desired thing will be achieved. And after the event is over, the prospective bride must also be ready with some changes in her. But this desire to be perfect sometimes stresses the couple and produces some pre-marital problems that sometimes neither partner realizes. Some of the conflicts that arose in this pre-marital affair, which even led to the failure of their wedding planning. The failure of the marriage of the bride and groom will certainly make the problem even bigger. There are also couples who can go through the pre-marital period but when they are married they will bring up the pre-marital problems they have experienced. Of course it will have a negative effect on the harmony of the household they foster. One way that can be done to minimize problems in pre-wedding prospective brides is with pre-marital counseling. Premarital counseling is given to minimize these negative impacts.